Factors affecting nutritional knowledge, attitude, practices and dietary intake among national players in Kathmandu, Nepal: a cross-sectional study - Madhu Thapa; Arjun Neupane; Sailendra Kumar Duwal Shrestha; Prabin Nepal; Atul Upadhyaya; Pratik Niraula; Ram Kumar Shrestha; Dev Ram Sunuwar (BMC, 2023)
Abstract Introduction Good nutrition knowledge and nutrient intake have been regarded as significant determinants in enhancing athletes' performance and overall health status. This study aimed to assess knowledge, attitude, and practices of nutrition and dietary intake among athletes. Methods A cross-sectional study was conducted from January to April 2022 among national athletes from two sports clubs in Kathmandu Metropolitan City, Nepal. A semi-structured questionnaire was used to collect the data. Anthropometric measurements and dietary intake were recorded. Bivariate and multivariate binary logistic regression was used to estimate the crude odds ratios (cOR), and adjusted odds ratios (aOR) with 95% confidence intervals (CIs). Results A total of 270 players were included in this study (mean age, 25 years; 49.6% male, 50.4% female). Almost half of the athletes had good nutrition knowledge [54.1% (146/270)], attitude [56.7% (153/270)], and practices [50% (135/270)] scores. The mean energy, carbohydrate, protein, and fat intake were 35.0 kcal/kg/day, 5.6, 0.9, and 0.9 g/kg/day, respectively. Likewise, mean calcium and iron intake were 370, and 12.5 mg, respectively. In the multivariate model, families with monthly household income less than 50,000 Nepalese rupees ($400) (adjusted Odds Ratio/aOR = 2.58; 95% CI: 1.12 to 5.96), and those who did not receive diet plan (aOR = 3.14; 95% CI: 1.25 to 7.84) were more likely to have poor nutrition knowledge. Players who did not check food labelling (aOR = 1.44; 95% CI: 0.78 to 2.63) were more likely to have negative attitude towards nutrition. Players who did not ever attend nutrition class (aOR = 3.54; 95% CI: 1.46 to 8.54) and those who did not consume different food during off and on the season of sports (aOR = 2.36; 95% CI: 1.39 to 4.01) were more likely to have poor nutrition practice. Conclusions Half of the athletes' nutritional knowledge, attitudes, and practices score were satisfactory. Nutrient intake among athletes was suboptimal. Nutrition intervention programs are critical to improve nutritional knowledge, attitude and practice related to dietary intake among national athletes in Nepal.